Effect of Imaging Markers on Reperfusion Therapy in Basilar Artery Occlusion. Issue 1 (4th May 2022) - Yan, Shenqiang; Zhou, Ying; Zhao, Yuqi; Wang, Feng; Tao, Anyang; Zhou, Lin; Pan, Mengxiong; Zhong, Genlong; Hu, Lingzhi; Jiang, Xuanfei; Mao, Xinlei; Tang, Huan; et al.
Abstract : Objective: We aimed to investigate the effectiveness of endovascular therapy (EVT) versus intravenous thrombolysis (IVT) in patients with basilar artery occlusion (BAO), based on the information of advanced imaging. Methods: We analyzed data of stroke patients with radiologically confirmed BAO within 24 hours. BAO subjects were categorized into "top‐of‐the‐basilar" syndrome (TOBS) and other types. An initial infarct size of <70ml and a ratio of ischemic tissue to infarct volume of ≥1.8 was defined as "target mismatch." The primary outcome was a good outcome, defined as a modified Rankin Scale score of 0 to 3 at 3 months. Propensity score adjustment and inverse probability of treatment weighting (IPTW) propensity score methods were used. Results: Among 474 BAO patients, 93 (19.6%) were treated with IVT prior to EVT, 91 (19.2%) were treated with IVT alone, 95 (20.0%) were treated with EVT alone, and 195 (41.1%) were treated with antithrombotic therapy. In IPTW analyses, we found no benefit of EVT over IVT for good outcome in either TOBS patients (odds ratio = 1.08, 95% confidence interval [CI] = 0.88–1.31) or those with other types (odds ratio = 1.13, 95% CI = 0.94–1.36). However, in patients with other types, if there existed a target mismatch, EVT was independently related to good outcome (odds ratio = 1.46, 95% CI = 1.17–1.81). Interpretation: The "target mismatch profile" seems to be a possible candidate selection standard of EVT for those with other types of BAO. Future studies should separate TOBS from other types of BAO, and try to use advanced imaging. ANN NEUROL 2022;92:97–106